Different characteristics of high and low transsphincteric fistulae. (June 2014) - van Onkelen, R. S.; Gosselink, M. P.; van Rosmalen, J.; Thijsse, S.; Schouten, W. R.
Abstract Aim Transsphincteric fistulae are classified as high or low. The aim of this observational study was to determine whether or not they have different characteristics. Method A consecutive series of 300 patients with a transsphincteric fistula of cryptoglandular origin was studied. Two hundred patients with a high transsphincteric fistula underwent transanal advancement flap repair and 100 patients with a low transsphincteric fistula underwent fistulotomy or ligation of the intersphincteric fistula tract at the Division of Colon and Rectal Surgery, Erasmus MC, Rotterdam. Various patient and fistula characteristics were assessed. Data were analysed by means of logistic regression. Results Low transsphincteric fistulae occurred more frequently in females (43% low transsphincteric fistulae vs 30% high transsphincteric fistulae; P < 0.05). The internal opening of these fistulae was predominantly located anteriorly (76% vs 18% in high transsphincteric fistulae; P < 0.001). Mean age at surgery was lower in patients with a low transsphincteric fistula (42 vs 47 years; P < 0.001). In these patients an associated abscess was observed in 4% compared with 54% of those patients with a high transsphincteric fistula (P < 0.001). In multivariate analysis, the differences between high and low transsphincteric fistulae regarding location of their internal opening and the presence of associated abscesses remained significant (P < 0.001). Conclusion Although not significant in multivariate analysis, low transsphincteric fistulae occur more frequently in younger patients and more often in females. These fistulae are predominantly located anteriorly and are rarely associated with an abscess. This was significant in univariate and multivariate analysis.